Supplementary material - Supplemental material for A New Chlorinated Phenolic Compound From the Antarctic Lichen, Pertusaria dactylina ... - Koo, Man H.; Kim, Min J.; Seo, Jae E.; Kim, Ji H.; Han, Se J.; Kim, Il C.; Lee, Jun H.; Youn, Ui J. (SAGE Journals, 2020)
Supplemental material, Supplementary material, for A New Chlorinated Phenolic Compound From the Antarctic Lichen, Pertusaria dactylina by Man H. Koo, Min J. Kim, Jae E. Seo, Ji H. Kim, Se J. Han, Il C. Kim, Jun H. Lee and Ui J. Youn in Natural Product Communications ...